THE RELATIONSHIP BETWEEN AGE, KNOWLEDGE AND HUSBAND'S SUPPORT WITH THE USE OF 3-MONTH DMPA INJECTABLE CONTRACEPTIVES IN FERTILE AGE COUPLES IN THE TEMBILAHAN HULU COMMUNITY HEALTH CENTER AREA - Susi Ernawati; Juda Julia Kristiarini; Risnawati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: 3-month injectable contraception is a contraceptive device in the form of a liquid containing the hormone progesterone which is injected into a woman's body periodically. DMPA (Depo Medroxy Progesterone Acetat) or Depo Provera is given every three months at a dose of 150 milligrams injected IM. The purpose of this study: is to analyze the relationship between age and husband's knowledge and support for the use of injection contraception at the Tembilahan Hulu Community Health Center. Method: The research used was an analytical survey with a cross sectional approach. Research population of family planning acceptors at UPTD Tembilahan Hulu Community Health Center, Indragiri Regency, Riau Province. In June-August 2024. The sample size is 100 respondents. Univariate data analysis and bivariate analysis using the Chi Square test and Logistic Regression test. Results: The research results can be interpreted as finding that the calculated F value = 15.322 with a significance level of 0.000 < 0.05, which means there is a significant relationship between age and the husband's level of knowledge and support for the use of injectable contraception